(untitled) (Research, Society and Development, 2023)
This research aimed to describe the benefits of kinesiotherapy in the home physiotherapy treatment of spinal osteomyoarticular dysfunctions and injuries. This is an integrative review where the search for data was conducted in the databases Virtual Health Library (VHL), Latin American and Caribbean Literature on Health Sciences (LILACS), PubMed, Google Scholar and SCIELO. The following descriptors were searched: Physical therapy; Home treatment; Spine; Spinal diseases, and, using strategies for combining the terms. After filtering and analyzing the publications according to the inclusion and exclusion criteria, 8 articles were selected for this review. In the literature reviewed it was possible to observe that physical therapy for home care patients with spinal injuries or osteomyoarticular dysfunctions has several benefits, ranging from the ease of care at home for the patient, to the improvement of various factors such as pain, functional capacity, limitations, balance, range of motion and coordination, with a low cost and complexity compared to other levels of care. Another aspect of utmost importance for the achievement of these benefits were the actions and activities of orientation for these patients, both during the sessions and the orientations to be performed extra sessions.